Preferences and Behaviour of Gen Z Voters in the 2024 Indonesian Presidential Election - Hakim, Lukman; Hakim, Ikhsan (Universitas Muhammadiyah Ponorogo, 2024)
This study investigates the preferences and political behaviour of first-time voters in the 2024 elections, focusing on how religious beliefs, rationalism, and social media impact their political judgments. The primary objective of this research is to explore the factors influencing the political decisions of Generation Z voters, who constitute a significant demographic in the electoral process. The study aims to assess the extent to which social media platforms shape political awareness and decision-making while also examining the role of digital literacy in fostering informed political participation.The study employs a qualitative descriptive method using a cluster random sampling strategy, with approximately 204 University Ahmad Dahlan (UAD) students as respondents. The findings indicate that social media platforms, particularly Instagram and TikTok, have become the dominant sources of political information, reflecting a shift from traditional to digital media. First-time voters prioritize politicians with clear visions, goals, and concrete work programs over those engaging in negative campaigns. Additionally, the study highlights the challenges young voters face, including money politics and low political engagement at the local level. Despite these obstacles, the strong rejection of money politics and the commitment to clean democracy among youth voters demonstrate their potential to drive ethical and inclusive political reforms.Based on these findings, this study recommends enhancing digital literacy programs to equip young voters with critical thinking skills when consuming political content online. Future research should further explore the long-term effects of social media-driven political engagement and investigate how different digital platforms influence voter behaviour across diverse socio-political contexts. Expanding the study to a broader demographic beyond university students may also provide deeper insights into the evolving dynamics of youth political participation.